An impact assessment of treated distillery wastewater on selected biological components of a marine ecosystem. - Gicana, Ronnie G.
An impact assessment was conducted on the effect of treated alcohol distillery wastewater to fish, algae and bacteria representing the different trophic levels of a marine ecosystem. The research investigated the toxicity of wastewater to milkfish, its potential in hte biostimulation of Donalliela tertiolecta, and its effect in changing methanogenic population density., Results revealed that LC50 of the wastewater to milkfish was between 3.68 and 40.20% by volume, and lower wastewater concentrations resulted to an increase in specific growth rate of milkfish compared to the control. this result indicated that lower wastewater concentration was not toxic to fishes even at chronic exposure. The biostimulation test revealed that the wastewater concentration resulting to significantly higher degree of algal specific growth was between 0.8 to 1.6% v/v. Concentrations higher than 1.6% proved toxic to the algae. Among the decomposers, the results indicated that at 9.0% v/v wastewater, microbial reproduction was stimulated, however, at higher concentrations, the wastewater became toxic to the methanogens.